A Study of Church Intervention in the Lives of the Children of Separated Parents: A Case of Paidha Parish, Nebbi Diocese of the Church of Uganda - Walter Cwinyaai (Uganda Christian University, 2025)
Parental separation and divorce have become increasingly common in today’s society, affecting millions of children worldwide. A descriptive study was carried out in Zombo district with the aim of establishing Church intervention in the lives of children of separated parents in Paidha Parish, Nebbi Diocese. Data was collected by use of questionnaires to gather empirical data. The findings revealed that the children of separated parents in Paidha parish face a number of challenges including: lack of basic needs, lack of parental love and anger, anxiety and emotional stress, poor performance in academics, depressive symptoms, poor health and malnutrition, low self-esteem, conduct problems, lack of parental care and guidance. The church is focusing on teaching the principles of safety and welfare of children affected by separation of parents, providing counselling services for separated parents to bring them together, offering prayer and support to children of separated parents and providing mentorship programs for skilling of affected children. The respondents suggested that the church should create supportive environment for children affected by the separation of their parents, have active programs such as care for kids of the divorced, active outreach and home visits for families, pastoral and emotional support for the affected children, encouraging heathy communication while allowing Bible-based healing through Bible study. All these would enable the church to grow strong, united, with godly instruction from every home, having holistic integration of faith and the homes would be transformed into little gospel outposts. The study recommended that the church should offer a Christian perspective that acknowledges and addresses the pain of separation, while providing a path toward healing by demonstrating healthy relationships and communication within the church community.